1985
DOI: 10.1037/0735-7044.99.2.381
|View full text |Cite
|
Sign up to set email alerts
|

Orienting response and detection of thalamic stimulation: Mechanism of perceptual learning in the cat.

Abstract: Naive cats cannot use thalamic stimulation as a signal to perform a behavioral response when stimulus intensities are too weak to evoke orienting behavior. Responses are quickly learned at higher intensities of stimulation, and with continued training, the cats become able to response to the weaker, previously ineffective stimulus. This increase in sensitivity is not due to changes in tonic arousal and appears to be relatively specific to the stimulated nucleus. The procedures may be useful in exploring the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In addition, cats and humans demonstrate a curvilinear rate of learning these discriminations as a function of test item complexity, with eight-sided figure pairs being the easiest (White & Ward, 1988). Bourassa and Weiden's (1985) investigations of orienting responses and detection of thalamic stimulation also demonstrated that mechanisms of perceptual learning in the cat are consistent with those reported in humans. Bourassa and Weiden concluded by suggesting that input to cerebral cortex from sensory organs in either species is not a sufficient condition to produce conscious experience or discrimination.…”
Section: Similarities Between Cats and Humansmentioning
confidence: 53%
“…In addition, cats and humans demonstrate a curvilinear rate of learning these discriminations as a function of test item complexity, with eight-sided figure pairs being the easiest (White & Ward, 1988). Bourassa and Weiden's (1985) investigations of orienting responses and detection of thalamic stimulation also demonstrated that mechanisms of perceptual learning in the cat are consistent with those reported in humans. Bourassa and Weiden concluded by suggesting that input to cerebral cortex from sensory organs in either species is not a sufficient condition to produce conscious experience or discrimination.…”
Section: Similarities Between Cats and Humansmentioning
confidence: 53%